Characterization of DAT missense mutations in novel mouse models - Berlin,Frida (2017)
The dopamine transporter (DAT) is responsible for dopamine (DA) clearance in the synaptic cleft, and thus crucial for maintaining DA homeostasis in the central nervous system (CNS). Mutations in the DAT coding gene have been associated with both movement and psychiatric disorders, such as parkinsonism and attention-deficit hyperactivity disorder (ADHD). However, the detailed contribution of DAT in human disease development is yet poorly understood. In the present study, we performed in vivo and ex vivo experiments to investigate the role of two DAT missense mutations, DAT I312F and DAT-D421N, that previously have been identified in a single patient diagnosed with a unique combination of both early onset parkinsonism and ADHD. Knock in mice homozygous for either DAT-I312F or DAT-D421N or compound heterozygous for the two mutations, corresponding to the patient genotype, were investigated. Striatal synaptosomes isolated from the three mice strains revealed dramatic reductions in DA uptake capacity for all three strains (Vmax: I312F = 61%, IFxDN = 24% and D421N = 10% of WT Vmax). Furthermore, confocal imaging of immunolabelled coronal brain slices displayed an apparent stronger immunosignal for striatal DAT in I312F KI mice, whereas the dopaminergic network in D421N KI mice showed reduced density, maybe reflecting neurodegeneration. Together these findings suggest that the two DAT mutations lead to altered DAT function and cause distinct DAergic dysregulation. Altered DA homeostasis was suggested by behavioral studies where the DAT-I312F KI mice demonstrated drastic increased locomotor activity both horizontally and vertically, however, without any signs of motor dysfunction. The results from my thesis strengthens the link of the two DAT missense mutations as risk factors for both ADHD and neurodegenerative early-onset parkinsonism and contribute to the insight of DAergic associated pathologies.